Testing self-adaptive applications with simulation of context events - Kakousis, Konstantinos; Paspallis, Nearchos; Papadopoulos, George; Ruiz, Pedro (Electronic Communications of the EASST, 2010)
Modern trends in mobile computing have raised the expectations of users in terms of such features such as context-awareness and self-adaptiveness. With such capabilities, applications can autonomously sense their context and automate a number of tasks, effectively reducing the attention required by the end users. This paper presents a custom simulation engine, designed to support the testing of applications developed using the MUSIC platform. The simulation tool consists of a platform-independent server module, deployed along with the application, and a client module which is responsible for interpreting and executing the simulation script. The use of the tool is demonstrated in the scope of the SatMotion application, which is designed to assist satellite antenna installers with specialized functionality.